Modeling impact of climate change on water resources and agriculture demand in the Volta Basin and other basin systems in Ghana - Barnabas A. Amisigo; Alyssa McCluskey; Richard Swanson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
An assessment of the impacts of projected climate change on water availability and crop production in the Volta Basin and the southwestern and coastal basin systems of Ghana has been undertaken as a component of the impacts and adaptation study for Ghana by UNU-WIDER and the University of Ghana. Four climate change scenarios were considered in addition to a reference (no change) scenario - two dry and two wet scenarios. The CliRun water balance model was used to simulate catchment runoffs using projected rainfall and temperature under the scenarios. The water evaluation and planning software was used for the water allocation modeling. The climate impacts on yields of many of the economically important Ghana crops were modeled using the AquaCrop software. The results show that all water demands (municipal, hydropower, and agriculture) cannot be simultaneously met under any of the scenarios used, including the wet scenarios. This calls for an evaluation of groundwater as an additional source of water supply and an integrated water resources management in the catchments to balance demand with supply and ensure sustainable socio-economic development. In addition, the AquaCrop model forecasts negative impacts for the crop yields studied, with some crops and regions seeing larger impacts than others.
Keywords: O55; Q54; 330; Ghana; water resources; agriculture; climate change